Homogeneous catalyst modifier for alkyne semi-hydrogenation: systematic screening in an automated flow reactor and computational study on mechanisms. Issue 8 (25th May 2022) - Asano, Shusaku; Adams, Samuel J.; Tsuji, Yuta; Yoshizawa, Kazunari; Tahara, Atsushi; Hayashi, Jun-ichiro; Cherkasov, Nikolay
Abstract : 21 types of modifiers are screened for palladium catalysed semi-hydrogenation of alkynes with varying catalyst type, reaction time, and target substrate using an automated flow reactor system. Abstract : The selectivity of palladium catalysed hydrogenation can be improved by adding a homogeneous modifier (or poison) such as quinoline to the reaction mixture. Although such selectivity improvement by modifiers (selective catalyst poisoning) has been known for decades, we still know little about them. We, ultimately, cannot select a modifier to improve a particular process. In this study, 21 types of modifiers are screened for the semi-hydrogenation of alkynes with varying catalyst type, reaction time, and target substrate using an automated flow reactor system. All of the studied variables changed affected hydrogenation activity and selectivity confirming the effectiveness of a multi-parameter optimization. 1, 10-phenanthroline marked the best selectivity beyond quinoline. The density functional theory (DFT) calculations suggest that 1, 10-phenanthroline has a remarkable ability to adsorb on the irregular surface of the catalyst that effects undesirable reaction.